ISSO É O QUE NOS MOVE! UMA ANÁLISE DE CONTEÚDO DA SÉRIE INSTITUCIONAL DOS CORREIOS E SEU PAPEL COMO FERRAMENTA DE INCLUSÃO À CIDADANIA - BIZAN, INGRID PFÜTZENREUTER CASTANHO (2020)
The present research intends to investigate in what way the series Isso é que nos move! from Correios build a narrative that privileges the company's services as a tool for inclusion to citizenship. We use as a theoretical reference Maurice Halbwachs and Pierre Nora to support memory studies, Muniz Sodré with sensitive strategies, Nestor García Canclini and Marshall Mcluhan for hybridization in the media in order to explain the choice of meta and not television, for example, Manuel Castells to support the importance of the Internet in the current communication process, Paulo Roberto Nassar with the necessary theory related to organizational communication and the impacts and relationships of metanarratives and micronarratives, besides José Murilo de Carvalho, Hanna Arendt, Thomas H. Marshall and Jung Mo Sung, as a subsidy of citizenship theme. We perform a content analysis of the institutional advertising series called Isso é o que nos move!, according to the proposal of Laurence Bardin, and we obtained proof of our hypothese once in all videos analyzed the corporate message is about the inclusion to citizenship.